Subjective Norms and Perceived Management Response to Whistle-Blowing: Evidence from Public Institutions of Uganda (Journal of Governance and Development (JGD), 2016)
The study focused on perceptions of management response to whistleblowing by employees and the way they are explained by their whistleblowing social norms and attitudes. Social norms consisted of social reprisal, awareness of serious wrongdoing, existence of whistleblowing support systems and accuracy of whistleblowing information. Other variables were the position of a wrongdoer in the organisation and organisational workforce size. The study was carried out in Sab-Saharan Africa using evidence from public institutions of Uganda. A quantitative, exploratory and descriptive research design was adopted and data were collected using self-administered questionnaires through simple random sampling of respondents. Findings were that perceptions of management response to whistleblowing by employees were negative. It was also revealed that employees, perceived accuracy of whistleblowing information was inaccurate, perceived social reprisals and serious wrongdoing exist in the organisations. Whistleblowing support systems were perceived to be lacking and employee attitudes to whistleblowing were negative. Perceptions on existence of whistleblowing support systems mediated between employee whistleblowing attitudes and perceptions of management response to whistleblowing by employees. A hierarchical linear regression on perceived management response to whistleblowing by employees was predicted by position of the wrongdoer, employee whistleblowing attitudes; and their perceived whistleblowing social reprisals, accuracy of whistleblowing information and availability of support systems. The predictors explained about 42 percent of the employee perceptions of management response to whistleblowing. These findings have policy and managerial implications as discussed.